A mixed-methods cross-cultural study of teacher care and teacher-student rapport in Iranian and Polish University students' engagement in pursuing academic goals in an L2 context. (June 2022) - Derakhshan, Ali; Doliński, Dariusz; Zhaleh, Kiyana; Enayat, Mostafa Janebi; Fathi, Jalil
Abstract: A convergent parallel mixed-methods approach was used to explore teacher care, teacher-student rapport, and engagement in pursuing academic goals in a foreign language (L2) context, as perceived by 223 Iranian and 208 Polish L2 students. Quantitative data were obtained through three scales, the cross-cultural validity and factor structure of which were ensured through testing measurement invariance and confirmatory factor analysis, respectively. The structural equation modeling results obtained through running Mplus approved that care and rapport predicted Iranian and Polish students' engagement in pursuing academic goals in an L2 context. For checking the equality of the structural path coefficients, the Omnibus Wald test was employed. Group differences in factor means were tested, showing that Iranian and Polish students differed significantly regarding their levels of engagement. Qualitative data, obtained through running interviews with 30 Iranian and 24 Polish students, selected from the initial sample, approved the predictive links of care and rapport with Iranian and Polish students' engagement in pursuing academic goals in an L2 context. However, the students' qualitative reports revealed how their perceived country's cultural and instructional contexts influenced their engagement, empirically supporting the supposition that engagement is the by-product of the dynamic interaction between the individual factors and the instructional context, necessitating the examination of the role of sociocultural values and home culture in accomplishing this educational objective.